A method for preparing a polyimide-based organic silicon composite membrane for pervaporative dehydration of isopropyl alcohol

CN117379997BActive Publication Date: 2026-11-03TIANJIN POLYTECHNIC UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311536828.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-17
Publication Date
2026-11-03
Estimated Expiration
2043-11-17

AI Technical Summary

Technical Problem

Existing organosilicon composite membrane preparation processes are complex and have poor repeatability, and there are problems such as raw material waste and decreased separation performance. In particular, it is difficult to achieve uniformity and controllable thickness in the application of pervaporation dehydration of isopropanol.

Method used

Ultrasonic spraying is used to deposit ultra-low viscosity silicone sol on the surface of polyimide substrate. By adjusting the solvent ratio and spraying parameters, the Marangoni effect is used to achieve uniform deposition and thickness control of the silicone layer, thereby reducing raw material waste.

Benefits of technology

The uniformity and thickness of the organosilicon composite membrane were made adjustable, reducing raw material waste and improving the separation performance of pervaporation dehydration of isopropanol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117379997B_ABST
    Figure CN117379997B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a polyimide-based organic silicon composite membrane for pervaporative dehydration of isopropyl alcohol, and belongs to the technical field of organic silicon composite membranes. The polyimide casting solution is prepared from polyimide and N,N-dimethylformamide, then is poured on non-woven fabric, scraped and phase-transformed to obtain a porous polyimide ultrafiltration membrane, and dried to obtain a porous polyimide-based membrane; the organic silicon sol is sprayed on the surface of the porous polyimide-based membrane by ultrasonic spraying, and is heat-cured to obtain the polyimide-based organic silicon composite membrane. The liquid is gently coated on the surface of the substrate by ultrasonic spraying, and the splashing rebound phenomenon does not occur, the uniformity of film formation is more easily controlled, and material waste can be reduced; the organic silicon sol is a double-solvent system of isopropyl alcohol and water, which is beneficial to forming a uniform and complete organic silicon active layer on the surface of the substrate through the Malan-goni effect, and finally realizes the ultrathin, uniform and defect-free preparation of the microporous organic silicon active layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organosilicon composite membrane technology, and in particular to a method for preparing a polyimide-based organosilicon composite membrane for pervaporation dehydration of isopropanol. Background Technology

[0002] Currently reported preparation processes for organosilicon composite membranes include thermal coating, spin coating, liquid diffusion, spraying, and thermal plasma chemical vapor deposition. Among these, thermal coating almost exclusively uses inorganic materials such as Al2O3 as the support, and its complex preparation process, poor reproducibility, and high cost limit its application. Spin coating has specific requirements regarding the affinity between the support and the sol, surface smoothness, and the size and shape of the base film, thus limiting its application to laboratory-scale organosilicon membrane preparation research. Liquid diffusion methods struggle to control the thickness of the BTESE layer and suffer from poor experimental reproducibility. Sol-gel spraying, due to the presence of airflow during spraying, causes the sol droplets to splash onto the substrate, making it difficult to control the uniformity of the functional layer and resulting in unnecessary material waste. In thermal plasma chemical vapor deposition, the organic groups in the organosilicon network are easily decomposed, leading to a decrease in membrane separation performance. Summary of the Invention

[0003] In view of this, the present invention provides a method for preparing a polyimide-based silicone composite membrane for pervaporation dehydration of isopropanol. The method utilizes a fine ultrasonic spraying method (ultrasonic atomization and spray deposition) to gently deposit ultra-low viscosity silicone sol onto the surface of a polyimide substrate. The prepared silicone layer is uniform, complete, and has an adjustable thickness. Moreover, it can reduce raw material waste compared to the traditional spraying method.

[0004] The present invention provides a method for preparing a polyimide-based silicone composite membrane (XP84-BTESE membrane) for pervaporation dehydration of isopropanol, comprising the following steps:

[0005] (1) Preparation of polyimide casting solution: The polyimide was vacuum dried to remove the residual moisture in the raw material. Then it was mixed with N,N-dimethylformamide and sealed. The mixture was placed in an oil bath and heated and stirred at 50°C until completely dissolved to obtain the polyimide casting solution. The solution was placed in a desiccator overnight to remove air bubbles.

[0006] (2) Preparation of porous polyimide ultrafiltration membrane: Under constant temperature and humidity conditions, the polyester nonwoven fabric is flattened and fixed on a clean glass plate. Then, the polyimide casting solution with degassed bubbles in step (1) is slowly poured onto the nonwoven fabric, the membrane is scraped, and the scraped membrane is immediately immersed in a pure water coagulation bath at 21°C for 20 minutes to complete the phase transformation. Then, the membrane is transferred to clean deionized water and soaked for 1 hour to fully remove the residual casting solution solvent in the membrane, and a porous polyimide ultrafiltration membrane with a smooth surface and no defects is obtained.

[0007] (3) Preparation of porous polyimide-based membrane: The porous polyimide ultrafiltration membrane prepared in step (2) is fixed and placed in an oven for heat treatment to obtain the porous polyimide-based membrane (XP84 base membrane);

[0008] (4) Preparation of porous polyimide-based silicone composite film: Fix the porous polyimide-based film prepared in step (3), and use ultrasonic spraying method to set the spraying flow rate to 0.3-0.5 mL / min and the substrate temperature to 30-70℃. Spray silicone sol onto the surface of the porous polyimide-based film. After the solvent has completely evaporated, repeat the ultrasonic spraying step. After spraying 1-3 times, heat cure the composite film at 150-200℃ for 10 min to obtain the polyimide-based silicone composite film.

[0009] Preferably, the polyimide vacuum drying in step (1) is performed at 110-130°C for 10-15 hours.

[0010] Preferably, the mass ratio of polyimide to N,N-dimethylformamide in step (1) is 20-25:70-80.

[0011] Preferably, the constant temperature and humidity conditions described in step (2) are: an ambient temperature of 21°C and an ambient humidity of 20% RH.

[0012] Preferably, the thickness of the film scraped in step (2) is 250 μm.

[0013] Preferably, the heat treatment temperature in step (3) is 150-200°C and the heat treatment time is 10-15 min.

[0014] Preferably, the organosilicon sol in step (4) is obtained by mixing sesquioxane monomer with isopropanol, adding deionized water and hydrochloric acid catalyst under continuous stirring, heating in a water bath, and completing the reaction to obtain organosilicon polymer sol.

[0015] More preferably, the ratio of isopropanol to deionized water in the organosilicon sol is 73-82:9-18; the sol concentration in the organosilicon sol is 5.0 wt%; and the molar ratio of HCl to silsesquioxane monomer in the hydrochloric acid catalyst is 0.01:1.

[0016] Preferably, in the ultrasonic spraying described in step (4), the spraying parameters are set as follows: spraying height 60mm, left and right speed 10000mm / min, front and back step 2mm, front and back speed 10000mm / min, left and right stroke 110mm.

[0017] Compared with existing technologies, the present invention has the following advantages: The present invention provides a method for preparing a polyimide-based organosilicon composite membrane for pervaporation dehydration of isopropanol. Ultrasonic spraying is used, where the liquid is gently coated onto the substrate surface without sputtering or rebound, making it easier to control the uniformity of film formation and reducing material waste. Furthermore, the organosilicon sol is a dual-solvent system of isopropanol and water. The Marangoni effect of this dual-solvent system is beneficial for forming a uniform and complete organosilicon active layer on the substrate. The present invention utilizes the Marangoni effect generated by silica sol microdroplets on the interface layer surface, and further enhances the Marangoni flow rate of the sol microdroplets generated by ultrasonic atomization on the polyimide interface by adjusting the ratio of the two solvents in the sol. This ultimately achieves the preparation of an ultra-thin, uniform, and defect-free microporous organosilicon active layer. Attached Figure Description

[0018] Figure 1 SEM images of the surface and cross-section of the XP84-BTESE films prepared in Examples 1, 2, and 3;

[0019] Figure 2 The PV performance graphs are for XP84-BTESE films prepared with different binary solvent (IPA / H2O) ratios in the sols of Examples 1, 4, and 5.

[0020] Figure 3 SEM images of the surface and cross-section of the XP84-BTESE films prepared in Examples 1, 4, and 5;

[0021] Figure 4 The PV performance graphs for XP84-BTESE films prepared at different substrate temperatures in Examples 1, 6, and 7 are shown.

[0022] Figure 5 SEM images of the surface and cross-section of the XP84-BTESE films prepared in Examples 1, 6, and 7;

[0023] Figure 6 The graphs show the PV performance of XP84-BTESE films prepared with different spraying flow rates in Examples 1, 8, and 9.

[0024] Figure 7 SEM images of the surface and cross-section of the XP84-BTESE films prepared in Examples 1, 8, and 9. Detailed Implementation

[0025] The present invention will be further described below with reference to the embodiments.

[0026] Example 1

[0027] A method for preparing a polyimide-based silicone composite membrane (XP84-BTESE membrane) for pervaporation dehydration of isopropanol, comprising the following steps:

[0028] (1) Preparation of polyimide casting solution: First, the polyimide raw material was vacuum dried at 120℃ for 12h to fully remove residual moisture. Then, 22g of the dried polyimide raw material (P84) was placed in a clean blue-mouth bottle, and 78g of N,N-dimethylformamide (DMF) was added to the bottle. Next, the blue-mouth bottle was tightened and placed in an oil bath. The mixture was heated and stirred at 50℃ until the P84 raw material particles were completely dissolved in DMF to obtain the casting solution. Finally, the casting solution was placed in a desiccator overnight to remove air bubbles.

[0029] (2) Preparation of porous polyimide ultrafiltration membrane: The porous polyimide ultrafiltration membrane was prepared in a constant temperature and humidity walk-in chamber. The ambient temperature in the walk-in chamber was set at 21℃ and the ambient humidity at 20%RH. The porous polyimide ultrafiltration membrane was prepared by phase inversion method. First, the polyester nonwoven fabric was flattened and fixed on a clean glass plate. Then, the P84 casting solution was slowly poured on the nonwoven fabric and the membrane was scraped to form a membrane with a thickness of 250μm. Next, the scraped membrane was immediately immersed in a pure water coagulation bath at 21℃ and kept for 20min to complete the phase inversion process. Then, the membrane was transferred to clean deionized water and soaked for 1h to fully remove the residual casting solution solvent in the membrane. Finally, a porous polyimide ultrafiltration membrane with a smooth and defect-free surface was obtained.

[0030] (3) Preparation of XP84 base membrane: The porous polyimide ultrafiltration membrane was fixed with a steel plate mold and placed in an oven at 150℃ for 10 min to obtain XP84 base membrane.

[0031] (4) Preparation of porous polyimide-based silicone composite film: The XP84 base film was flattened and fixed on the heating table of the ultrasonic spraying equipment with transparent tape, and the silicone sol was sprayed onto the surface of the XP84 film by ultrasonic spraying.

[0032] The organosilicon sol is prepared by mixing silsesquioxane monomers with isopropanol, heating in a water bath, adding deionized water and hydrochloric acid catalyst under continuous stirring, and obtaining an organosilicon polymer sol after the reaction is complete; the ratio of isopropanol to deionized water in the organosilicon sol is 73:9; the sol concentration in the organosilicon sol is 5.0 wt%; and the molar ratio of HCl to silsesquioxane monomer in the hydrochloric acid catalyst is 0.01:1.

[0033] In the ultrasonic spraying process, the ultrasonic spraying equipment was selected to use left and right spraying mode, and the spraying parameters were set as follows: spraying height: 60mm, left and right speed: 10000mm / min, forward and backward step: 2mm, forward and backward speed: 10000mm / min, left and right stroke: 110mm; spraying flow rate: 0.4mL / min, substrate temperature: 30℃. After the solvent in the sol on the film surface has completely evaporated, the ultrasonic spraying steps were repeated. After spraying 3 times, the composite film was heat-cured at 200℃ for 10min and then taken out to finally obtain the XP84-BTESE film.

[0034] Examples 2-9

[0035] By changing the parameters of the mass ratio of isopropanol and deionized water in the organosilicon sol, the spraying flow rate, the substrate temperature, and the number of spraying times in step (4) of Example 1, a polyimide-based organosilicon composite membrane for pervaporation dehydration of isopropanol was prepared. Other steps were the same as in Example 1. The specific parameters in Examples 1 to 9 are shown in Table 1.

[0036] Table 1

[0037]

[0038] As can be seen from Table 1, Examples 1, 2, and 3 investigated the effect of the number of spraying cycles on the XP84-BTESE film; Examples 1, 4, and 5 investigated the effect of the mass ratio of isopropanol and deionized water in the organosilicon sol on the XP84-BTESE film; Examples 1, 6, and 7 investigated the effect of substrate temperature on the XP84-BTESE film; and Examples 1, 8, and 9 investigated the effect of spraying flow rate on the XP84-BTESE film.

[0039] Surface and cross-sectional SEM images of the XP84-BTESE films prepared in Examples 1, 2, and 3 are shown below. Figure 1 .from Figure 1 It can be seen that the surface morphology of the silicone functional layer is uniform and complete. With the increase of the number of spraying times, the hollow defects in the silicone functional layer gradually decrease. When the number of spraying times is 3, the hollow defects in the silicone functional layer disappear. This is because during the coating process, the silicone sol can compensate for the hollow defects generated by the previous coating layer.

[0040] The PV performance graphs of XP84-BTESE films prepared with different binary solvent (IPA / H2O) ratios in the sols of Examples 1, 4, and 5 are shown below. Figure 2 .from Figure 2It can be seen that the permeation flux and separation factor still exhibit a trade-off effect. When the IPA content in the sol is fixed at 73 vol%, decreasing the water content in the sol increases the permeation flux of the XP84-BTESE membrane but decreases the separation factor. Compared with the sol with a binary solvent (IPA / H2O) ratio of 73:9, the XP84-BTESE membrane prepared with an IPA / H2O volume ratio of 73:18 is less stable, and the uneven deposition of the BTESE layer leads to poor separation performance. Keeping the water content in the sol constant, decreasing the IPA content reduces the permeation flux of the XP84-BTESE membrane.

[0041] Surface and cross-sectional SEM images of the XP84-BTESE films prepared in Examples 1, 4, and 5 are shown below. Figure 3 .from Figure 3 As can be seen from the surface morphology images, the membrane surface with an IPA / H2O volume ratio of 73:9 in the sol is the smoothest, indicating that the membrane prepared with this IPA / H2O ratio has the best uniformity. This membrane also exhibits the best pervaporation and isopropanol dehydration performance, verifying that the deposition effect of the BTESE layer has a significant impact on the separation performance of the organosilicon composite membrane. Organosilicon composite membranes prepared with sols using other binary solvent (IPA / H2O) ratios show obvious particulate agglomeration on their surfaces.

[0042] The PV performance graphs of XP84-BTESE films prepared at different substrate temperatures in Examples 1, 6, and 7 are shown below. Figure 4 ,from Figure 4 It can be seen that the separation factor and permeation flux of the XP84-BTESE membrane still exhibit a significant trade-off relationship with the substrate temperature. As the substrate temperature increases, the permeation flux gradually increases, while the separation factor gradually decreases. At a substrate temperature of 70℃, the sol droplets dry rapidly upon landing on the substrate, failing to diffuse quickly enough to reach areas not directly coated, resulting in defects in the silicone layer and a low separation factor for the XP84-BTESE membrane. When the substrate temperature drops to 50℃, the solvent evaporation time in the sol on the substrate surface increases, but the solvent evaporation rate is still significantly faster than the liquid flow rate, leading to an uneven and incomplete BTESE layer and poor separation performance. Further reducing the temperature to 30℃, the solvent evaporation rate and liquid flow rate on the substrate surface reach equilibrium, causing the droplets to fuse into a complete liquid film. Furthermore, the Marangoni effect allows the sol droplets to flow to areas not directly covered by the droplets, resulting in a complete and defect-free BTESE separation layer. The XP84-BTESE membrane prepared at a substrate temperature of 30°C exhibits the best separation performance.

[0043] Surface and cross-sectional SEM images of the XP84-BTESE films prepared in Examples 1, 6, and 7 are shown below. Figure 5 ,from Figure 5 As can be seen from the cross-sectional images of the film, the thickness of the BTESE layer changes significantly with increasing substrate temperature. At a substrate temperature of 70℃, the BTESE layer thickness is approximately 730 nm. When the substrate temperature is reduced to 50℃ and 30℃, the thicknesses are 400 nm and 300 nm, respectively, showing a decrease in thickness as the substrate temperature decreases. This is attributed to changes in the flow rate and evaporation rate of the sol on the substrate surface with varying substrate temperature. At 70℃, the solvent evaporation rate in the sol falling onto the substrate surface is very fast, and the droplets do not have enough time to diffuse outwards, resulting in a smaller coverage area of ​​the solute in the sol and a thicker BTESE layer. When the temperature drops to 50℃, the solvent evaporation rate in the droplets slows down, and the time for the droplets to diffuse outwards increases, thus reducing the thickness of the formed BTESE layer. When the substrate temperature is 30°C, the solvent evaporation rate and flow rate of the sol droplets reach equilibrium, forming a defect-free 300nm thick functional layer on the XP84 base film surface.

[0044] The PV performance graphs of XP84-BTESE films prepared with different spraying flow rates in Examples 1, 8, and 9 are shown below. Figure 6 ,from Figure 6 It can be seen that when the spraying flow rate is below 0.3 mL / min, the amount of sol falling on the substrate surface is too small, and the fine droplets cannot form a complete wet layer. The XP84-BTESE membrane prepared with a spraying flow rate of 0.3 mL / min has a better separation effect, with a separation factor of 950, indicating that the BTESE functional layer prepared at this flow rate is relatively complete. Therefore, 0.3 mL / min is considered to be the minimum spraying flow rate threshold for achieving pinhole-free sol coverage on the substrate. The XP84-BTESE membrane prepared with a spraying flow rate of 0.4 mL / min exhibits the best separation performance, with a flux of 0.49 kg / m³. 2 h, the separation factor increased to 1282, therefore we hypothesize that the separation factor of the silicone composite membrane also increases with increasing spray flow rate. However, when the spray flow rate was further increased to 0.5 mL / min, the membrane flux was 0.46 kg / m³. 2 h, the separation factor is 822. The thickness of the BTESE layer increases slightly with increasing spray flow rate. The silicone composite film did not exhibit a significant trade-off effect at these three spray flow rates. The reasons can be attributed to two main factors: First, the polymer base film shrinks during high-temperature heat treatment, and the silicone particles penetrating into the porous polymer pores provide support for the membrane pores. Within the spray flow rate range we used, the shrinkage of the base film pores and the supporting effect of the silicone particles within the membrane pores counterbalance each other, resulting in a less pronounced trade-off effect.

[0045] Surface and cross-sectional SEM images of the XP84-BTESE films prepared in Examples 1, 8, and 9 are shown below. Figure 7 ,from Figure 7 As can be seen from the SEM surface images, the surfaces of the silicone composite membranes prepared at the three spraying flow rates are very smooth and uniform, indicating that the spraying flow rate has little effect on the membrane surface morphology within the spraying range of 0.3-0.5 mL / min. The SEM cross-sectional images show that the thicknesses of the BTESE layer at spraying flow rates of 0.3, 0.4, and 0.5 mL / min are 200, 300, and 370 nm, respectively. With increasing spraying flow rate, the solute mass falling onto the base membrane surface also increases, thus the thickness of the BTESE functional layer gradually increases. Although the membrane prepared at a spraying flow rate of 0.3 mL / min has the thinnest BTESE layer, its pervaporation flux is not the highest in the pervaporation test. This may be because although the thinner BTESE layer reduces mass transfer resistance to some extent, polyimide is a polymer material, and severe pore formation occurs during high-temperature thermosetting, and the base membrane also has a significant impact on the pervaporation flux. XP84 membrane is a porous membrane. During the spraying process, some of the silicone sol will penetrate downward into the pores of the base membrane. When the BTESE layer is cured at a high temperature of 200℃, the silicone particles that have penetrated into the pores of the base membrane will support the membrane pores and reduce the pore shrinkage effect of the base membrane. Therefore, XP84-BTESE membrane does not show obvious trade-off effect.

[0046] The IPA / Water dehydration performance of the XP84-BTESE membranes prepared in Examples 1-9 was tested by pervaporation dehydration of a 90wt% isopropanol aqueous solution at 60°C. The results are shown in Table 2.

[0047] Table 2

[0048] <![CDATA[Flux [kg / m 2 h]]]> Separation factor Example 1 0.45 1282 Example 2 0.67 767 Example 3 0.71 726 Example 4 0.6 209 Example 5 0.71 140 Example 6 1.2 111 Example 7 1.34 94 Example 8 0.39 950 Example 9 0.46 822

[0049] from Figure 1-7 Based on the contents of Table 1-2, the following conclusions can be drawn:

[0050] As the number of spraying times increases, the penetration of the sol can compensate for minor defects in the previous layer. Appropriately increasing the number of coating times can improve the film formation effect. However, the thickness of the silicone functional layer increases with the number of spraying times, which increases the mass transfer resistance and reduces the permeation flux of the composite film. Furthermore, if the silicone layer is too thick, it is prone to cracking. The film formation effect is best when the number of spraying times is 3.

[0051] The ratio of the binary solvent (IPA / H2O) in the organosilicon sol has a crucial impact on the deposition effect of the BTESE functional layer. The ultra-low viscosity of the organosilicon sol makes it very difficult to achieve large-area uniform deposition of the organosilicon functional layer on a polymer substrate. In coating technology, it is necessary to reduce the surface tension of the liquid to improve the spreadability of the sol on the substrate surface, as it requires a smaller volume of liquid to completely cover the substrate, and the solvent in the liquid evaporates more uniformly. This invention uses a dual-solvent system of water and an organic solvent. The Marangoni effect of the dual-solvent system also promotes the formation of a uniform and complete liquid film. The Marangoni effect is used to diffuse the liquid to areas not directly covered by droplets. The main factors affecting the Marangoni linear velocity are surface tension, the volume fraction of the low surface tension liquid, and the evaporation rate of the binary solvent. The organosilicon composite membrane prepared with an IPA / H2O volume ratio of 73:9 exhibits the best separation effect.

[0052] Substrate temperature simultaneously affects the liquid rheological properties of the silicone sol on the substrate surface and the evaporation rate of the solvent in the sol, which is crucial to the BTESE layer performance and therefore an important factor influencing the separation effect of silicone composite membranes. When the substrate temperature is 30℃, the solvent evaporation rate and liquid flow rate on the substrate surface reach equilibrium, and the droplets merge to form a complete liquid film. Furthermore, the Marangoni effect allows the sol droplets to flow to areas not directly covered by droplets, resulting in a complete and defect-free BTESE separation layer.

[0053] To achieve complete, pinhole-free sol coverage of the substrate surface, it is necessary to investigate the minimum spray flow rate threshold required for complete sol coverage on the XP84 substrate membrane. Experiments revealed that 0.3 mL / min is the minimum spray flow rate threshold for achieving pinhole-free sol coverage. The XP84-BTESE membrane prepared with a spray flow rate of 0.4 mL / min exhibited the best separation performance, with a flux of 0.49 kg / m³. 2 h, the separation factor is 1282.

[0054] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a polyimide-based organosilicon composite membrane for pervaporation dehydration of isopropanol, characterized in that, Includes the following steps: (1) Preparation of polyimide casting solution: The polyimide was vacuum dried to remove residual moisture from the raw material. Then it was mixed with N,N-dimethylformamide and sealed. The mixture was placed in an oil bath and heated and stirred at 50°C until completely dissolved to obtain the polyimide casting solution. The solution was placed in a desiccator overnight to remove air bubbles. (2) Preparation of porous polyimide ultrafiltration membrane: Under constant temperature and humidity conditions, the polyester nonwoven fabric is flattened and fixed on a clean glass plate. Then, the polyimide casting solution with degassed bubbles in step (1) is slowly poured onto the nonwoven fabric, the membrane is scraped, and the scraped membrane is immediately immersed in a pure water coagulation bath at 21°C for 20 min to complete the phase transformation. Then, the membrane is transferred to clean deionized water and soaked for 1 h to fully remove the residual casting solution solvent in the membrane, and a porous polyimide ultrafiltration membrane with a smooth surface and no defects is obtained. (3) Preparation of porous polyimide-based membrane: The porous polyimide ultrafiltration membrane prepared in step (2) is fixed and placed in an oven for heat treatment to obtain the porous polyimide-based membrane; (4) Preparation of porous polyimide-based silicone composite film: Fix the porous polyimide-based film prepared in step (3), use ultrasonic spraying method, set the spraying flow rate to 0.3-0.5 mL / min, the substrate temperature to 30-70℃, spray silicone sol on the surface of porous polyimide-based film, after the solvent has completely evaporated, repeat the ultrasonic spraying step, spray 1-3 times, and then heat cure the composite film at 150~200℃ for 10 min to obtain the polyimide-based silicone composite film; The heat treatment temperature in step (3) is 150~200℃, and the heat treatment time is 10~15min; The organosilicon sol in step (4) is prepared by mixing silsesquioxane monomers with isopropanol, adding deionized water and hydrochloric acid catalyst under continuous stirring, heating in a water bath, and obtaining organosilicon polymer sol after the reaction is completed; the ratio of isopropanol to deionized water in the organosilicon sol is 73~82:9~18; the sol concentration in the organosilicon sol is 5.0wt%; the molar ratio of HCl to silsesquioxane monomer in the hydrochloric acid catalyst is 0.01:

1.

2. The method for preparing a polyimide-based organosilicon composite membrane for pervaporation dehydration of isopropanol according to claim 1, characterized in that, The polyimide vacuum drying in step (1) is performed at 110~130℃ for 10~15h.

3. The method for preparing a polyimide-based organosilicon composite membrane for pervaporation dehydration of isopropanol according to claim 1, characterized in that, The mass ratio of polyimide to N,N-dimethylformamide in step (1) is 20~25:70~80.

4. The method for preparing a polyimide-based organosilicon composite membrane for pervaporation dehydration of isopropanol according to claim 1, characterized in that, The constant temperature and humidity conditions described in step (2) are: ambient temperature of 21℃ and ambient humidity of 20 RH.

5. The method for preparing a polyimide-based organosilicon composite membrane for pervaporation dehydration of isopropanol according to claim 1, characterized in that, The thickness of the scraped film in step (2) is 250 μm.

6. The method for preparing a polyimide-based organosilicon composite membrane for pervaporation dehydration of isopropanol according to claim 1, characterized in that, In step (4) of ultrasonic spraying, the spraying parameters are set as follows: spraying height 60 mm, left and right speed 10000 mm / min, front and back step 2 mm, front and back speed 10000 mm / min, left and right stroke 110 mm.

Citation Information

Patent Citations

  • Method for preparing separation membrane by utilizing ultrasonic atomization and deposition method

    CN108854571A

  • Supported polysilsesquioxane membrane and production thereof

    US20140287156A1